Utilization of Knockout Mice to Examine the Potential Role of Gastric Histamine H2-Receptors in Menetrier's Disease - Toshiki Ogawa; Kazuhiko Maeda; Shunsuke Tonai; Takashi Kobayashi; Takeshi Watanabe; Susumu Okabe (Elsevier, 2003)
Menetrier's disease is characterized by giant gastric folds with foveolar hyperplasia and cystic dilatation, hypoproteinemia, and enhanced mucus secretion. The etiology remains unresolved and an effective treatment has yet to be established. Here we show that histamine H2-receptor deficient mice developed gastric pathophysiological changes resembling Menetrier's disease for up to 17 months of observation. Mutant mice were found to have an increased stomach weight, enlarged gastric folds with cystic dilatation, hypergastrinemia, hypoalbuminemia, increased mucus secretion and overexpression of mucosal transforming growth factor (TGF) α. Both a cholecystokinin (CCK)2-receptor antagonist and an epidermal growth factor (EGF)-receptor tyrosine kinase inhibitor significantly reduced the increase in stomach weight. It appears that lack or downregulation of histamine H2-receptors might be involved in the pathogenesis of Menetrier's disease.